2020
DOI: 10.3390/children7050047
|View full text |Cite
|
Sign up to set email alerts
|

Culinary Education Programs for Children in Low-Income Households: A Scoping Review

Abstract: Child obesity in the United States is at an all-time high, particularly among underserved populations. Home-cooked meals are associated with lower rates of obesity. Helping children develop culinary skills has been associated with improved nutrition. The purpose of this study is to report results from a scoping review of culinary education interventions with children from low-income families. Three databases and hand searches of relevant articles were examined. Retained articles met inclusionary criteria. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…The review found that youths who helped with meal preparation at home had high confidence in cooking and selecting healthy foods, as well as greater preferences for and consumption of healthy foods based on evidence from observational studies. A more recent scoping review demonstrated improvements in children's nutrition‐related outcomes after participating in healthy meal preparation interventions 16 . However, the scoping review focused specifically on children from low‐income households and included only quasi‐experimental studies and randomised‐controlled trials (RCT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review found that youths who helped with meal preparation at home had high confidence in cooking and selecting healthy foods, as well as greater preferences for and consumption of healthy foods based on evidence from observational studies. A more recent scoping review demonstrated improvements in children's nutrition‐related outcomes after participating in healthy meal preparation interventions 16 . However, the scoping review focused specifically on children from low‐income households and included only quasi‐experimental studies and randomised‐controlled trials (RCT).…”
Section: Introductionmentioning
confidence: 99%
“…A more recent scoping review demonstrated improvements in children's nutrition-related outcomes after participating in healthy meal preparation interventions. 16 However, the scoping review focused specifically on children from lowincome households and included only quasi-experimental studies and randomised-controlled trials (RCT).…”
mentioning
confidence: 99%
“…Es posible también que sea tiempo de replantear el modelo de implementación actual del PAEP que implica una actitud pasiva de los estudiantes y sus familia y escalar a modalidades que involucren a cuidadores y al propio niño aún en situación de (19) pobreza tal como se ha visto en otros países en los que mejoran no solo los indicadores nutricionales s i n o l a r e t e n c i ó n e s c o l a r y e l s e n t responsabilidad ante la autoalimentación además del redireccionamiento del enfoque educativo y participativo para mejoría la calidad de (22,23) la dieta de esta población .…”
Section: Discussionunclassified
“…Limited access to healthy food also presents a growing problem across the country. Americans living in low-income and minority areas tend to have poor access to healthy food 7,9 . Having a poor selection of healthy foods and a wide variety of unhealthy foods contributes to poor diet, obesity, and other chronic diseases 10 .…”
mentioning
confidence: 99%